2012
DOI: 10.1371/journal.pone.0035883
|View full text |Cite
|
Sign up to set email alerts
|

ProBDNF Collapses Neurite Outgrowth of Primary Neurons by Activating RhoA

Abstract: BackgroundNeurons extend their dendrites and axons to build functional neural circuits, which are regulated by both positive and negative signals during development. Brain-derived neurotrophic factor (BDNF) is a positive regulator for neurite outgrowth and neuronal survival but the functions of its precursor (proBDNF) are less characterized.Methodology/Principal FindingsHere we show that proBDNF collapses neurite outgrowth in murine dorsal root ganglion (DRG) neurons and cortical neurons by activating RhoA via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 66 publications
(96 reference statements)
7
114
0
Order By: Relevance
“…Our previous study showed that the neurite outgrowth of dorsal root ganglion neurons in vitro is inhibited upon treatment with proBDNF, but enhanced upon treatment with anti-proBDNF (Sun et al, 2012). As this anti-proBDNF antibody can neutralize the biological activities of proBDNF in neurons (Fan et al, 2008;Sun et al, 2012;Xu et al, 2011), we wished to establish whether anti-proBDNF treatment can reverse the behavioral and pathological impairments in rats caused by chronic stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed that the neurite outgrowth of dorsal root ganglion neurons in vitro is inhibited upon treatment with proBDNF, but enhanced upon treatment with anti-proBDNF (Sun et al, 2012). As this anti-proBDNF antibody can neutralize the biological activities of proBDNF in neurons (Fan et al, 2008;Sun et al, 2012;Xu et al, 2011), we wished to establish whether anti-proBDNF treatment can reverse the behavioral and pathological impairments in rats caused by chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…As this anti-proBDNF antibody can neutralize the biological activities of proBDNF in neurons (Fan et al, 2008;Sun et al, 2012;Xu et al, 2011), we wished to establish whether anti-proBDNF treatment can reverse the behavioral and pathological impairments in rats caused by chronic stress. The present study showed that i.c.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ProBDNF is synthesized and subsequently cleaved, either intracellularly, by prohormone convertases and furin, or extracellularly, by plasmin and matrix metalloproteinases (MMPs), to generate mature BDNF (6,7). Mature BDNF and proBDNF exert opposing effects through two different transmembrane receptor signaling systems, consisting of tyrosine receptor kinase B (TrkB) and p75 neurotrophin receptor (p75NTR) to modulate cell apoptosis (8)(9)(10), long-term depression (11) and synaptic plasticity (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we considered whether activation of RhoA, which is known to directly affect F-actin reorganization, was activated by NGF in Daoy-TrkA cells, whether it was localized to the macropinosome membranes, and whether it was essential to drive macropinocytosis. In this respect, RhoA activation has been shown to be associated with both neurite/dendritic extension and retraction in the nervous system (40,(65)(66)(67)(68)(69). We examined the kinetics of NGF-induced activation of RhoA in Daoy-TrkA cells using a GST fusion protein containing the Rho binding domain of rhotekin and observed RhoA activation as early as 10 min in response to NGF and peak activation at 6 h, and while the abundance of RhoA decreased by 12 to 24 h, the remaining molecules were still active (Fig.…”
Section: Resultsmentioning
confidence: 99%